Assessment of the European Commission's proposals for financing the EU budget in 2021-2027 - Elżbieta Kawecka-Wyrzykowska (International Journal of Management and Economics, 2020)
A major problem in all European Union (EU) budgetary negotiations is the approach of Member States in net return terms (the fair-return approach). EU members compare their contributions to the EU budget with transfers that they receive from the budget. Net payers tend to reduce the size of the budget to contribute less. Brexit has aggravated the problem of the size of revenue (due to the United Kingdom's position as a big net payer). Also, new expenditure needs have arisen (for protecting external borders and climate, innovation, etc.). To address those needs, in 2018, the Commission submitted three proposals to supplement the current resources to finance the EU budget after the expiry of the principles of the Multiannual Financial Framework (MFF) for 2014-2020 at the end of 2020. The article aims to indicate whether the Commission's proposals are good instruments for the financing of the EU budget. The assessment relies on selected criteria based on theory. It also takes account of the feasibility of the proposals. The main conclusion is that none of the proposals meets well theoretical criteria of "genuine" EU revenue. Also, for practical reasons, it will be difficult for the Member States to come to an agreement on new budgetary resources. All proposals would be relatively costly for Poland.
Keywords: H21; H61; H77; H87; 650; EU budget; EU Multiannual Financial Framework; own resources; EU taxes